Adaptive laboratory evolution enhances cell yield and lipid production of Chlorella sorokiniana under mildly cold conditions - Lu, Shu-Yi; Zhang, Shi-Yu; Zhang, Quan-Guo (Frontiers in Microbiology, 2025)
One challenge to large-scale microalgae cultivation, e.g., for biodiesel production, is the seasonal low-temperature conditions. We argue that seasonally varying selection in natural environments has prevented algae from better adapting to cold temperatures, and that laboratory evolution offers a promising approach for obtaining cold-adapted algal materials. We conducted a population-level artificial selection experiment with the unicellular green microalgae Chlorella sorokiniana at both a benign temperature (25 °C) and a mildly cold temperature (15 °C). Four artificial selection regimes were established: random selection, selection for high biomass (i.e., cell yield), selection for high lipid production, and rotation between high-biomass and high-lipid selection. The selection experiment lasted for 12 cycles of culture propagation; cell yield and lipid content were quantified by optical density (OD750) measurement and sulpho-phospho-vanillin (SPV) colorimetric method, respectively. We did not observe significant differences among the four selection regimes in evolutionary changes of algal cell yield or lipid yield, suggesting that natural selection at the individual level had dominated the evolutionary changes. Nevertheless, compared with the ancestral strain, selection lines that had evolved at 15 °C typically exhibited increased cell yield and reduced lipid content per cell, indicating a trade-off relationship. However, substantial increases in cell yield may compensate for the reduction in lipid content per cell. Notably, three out of 16 selection lines showed > 1-fold increase in cell yield, and one exhibited >1-fold increase in population-level lipid yield. Selection lines that had evolved at 25 °C exhibited even greater increases in both cell and lipid yields, with a positive relationship between cell yield and lipid content per cell. Our results demonstrated the potential for laboratory evolution to obtain algal materials suitable for biofuel production under seasonal low-temperature conditions.